Laccase-Driven Transformation of High Priority Pesticides Without Redox Mediators: Towards Bioremediation of Contaminated Wastewaters - Vaithyanathan, Vasanth Kumar; Vaidyanathan, Vinoth Kumar; Cabana, Hubert (Frontiers in Bioengineering and Biotechnology, 2022)
In this study, Pleurotus dryinus was grown on municipal biosolids (BS) as the substrate to produce laccase for the removal of pesticides (fungicides, herbicides, and insecticides) from wastewater. Among the various types of BS tested, sterilized biosolids (SBS) were the most promising substrate for laccase production by P. dryinus with a maximal laccase activity (162.1 ± 21.1 U/g dry substrate) followed by hygenized biosolids (HBS) (96.7 ± 17.6 U/g dry substrate), unsterilized biosolids (UBS) (31.9 ± 1.2 U/g dry substrate) and alkali treated biosolids (ABS) (8.2 ± 0.4 U/g dry substrate). Ultrasound assisted extraction of this enzyme from fermented UBS was carried out with 0.1M phosphate buffer at pH 7.0, which increased the enzyme activity of the crude extract by 30%. To test the catalytic potential of the biocatalyst in real matrices, 1 U/mL of recovered crude laccase extract was applied for 24 h for the removal of 29 pesticides (9 fungicides, 10 herbicides and 10 insecticides) either separately or as a mixture from spiked biologically treated wastewater effluent. When treated with crude enzyme extract, high priority herbicides, metolachlor and atrazine were completely removed, while 93-97% of the insecticides aldicarb, spinosad and azinphos-methyl and up to 91% of kresoxim-methyl were removed. Promising results were obtained with BS-derived crude enzyme extract exhibiting improved pesticide removal, which may be due to the mediator effect resulting from the catalytic transformation of other molecules in the cocktail. The results demonstrated a promising integrated bioprocess for the removal of pesticides in wastewater using crude laccase obtained from BS..